Targeting of retrovirus-derived Rtl8a/8b causes late-onset obesity, reduced social response and increased apathy-like behaviour - Yoshifumi Fujioka; Hirosuke Shiura; Masayuki Ishii; Ryuichi Ono; Tsutomu Endo; Hiroshi Kiyonari; Yoshikazu Hirate; Hikaru Ito; Masami Kanai-Azuma; Takashi Kohda; Tomoko Kaneko-Ishino; Fumitoshi Ishino (Open Biology)
Retrotransposon Gag-like (RTL) 8A, 8B and 8C are eutherian-specific genes derived from a certain retrovirus. They cluster as a triplet of genes on the X chromosome, but their function remains unknown. Here, we demonstrate that Rtl8a and Rtl8b play important roles in the brain: their double knockout (DKO) mice not only exhibit reduced social responses and increased apathy-like behaviour, but also become obese from young adulthood, similar to patients with late Prader–Willi syndrome (PWS), a neurodevelopmental genomic imprinting disorder. Mouse RTL8A/8B proteins are expressed in the prefrontal cortex and hypothalamus and localize to both the nucleus and cytoplasm of neurons, presumably due to the N-terminal nuclear localization signal-like sequence at the N-terminus. An RNAseq study in the cerebral cortex revealed reduced expression of several GABA type A receptor subunit genes in DKO, in particular Gabrb2, which encodes its β2 subunit. We confirmed the reduction of GABRB2 protein in the DKO cerebral cortex by western blotting. As GABRB2 has been implicated in the aetiology of several neurodevelopmental and neuropsychiatric disorders, it is likely that the reduction of GABRB2 is one of the major causes of the neuropsychiatric defects in the DKO mice.